An operational framework for wildlife health in the One Health approach - Goulet, C.; Garine-Wichatitsky, M. de; Chardonnet, P.; Klerk, L.-M. de; Kock, R.; Muset, S.; Suu-Ire, R.; Caron, Alexandre (Elsevier, 2024)
Wildlife is an essential component of biodiversity and provides people with multiple social and economic benefits. However, a resurgence of epidemics over the past two decades has highlighted wildlife's role as a potential source of dangerous pathogens for humans and livestock, with devastating consequences worldwide. Simultaneously, numerous reports have indicated that wildlife populations are declining at an alarming rate due to human and livestock pathogens, predation, and competition. An integrated approach to managing wildlife, human, and domestic animal health is therefore clearly needed. Yet this integration often fails to materialize due to a lack of wildlife health standards and know-how. Here, we present an operational framework that follows a step-by-step approach: i) a holistic definition of human health is adapted to the context of other-than-human animals, including wildlife; then, ii) different categories of wildlife living within a landscape or a country are defined based on the management systems under which they live. For each wildlife category, the type (natural vs. anthropogenic) of habitat, the nature of the interface of wildlife with humans and/or livestock, and the level of sanitary control are defined; and finally, iii) the holistic definition of wildlife health is considered in relation to each wildlife category to define health challenges and the domains of expertise required to address them. This framework can assist national and international agencies, including veterinary and wildlife authorities and policy makers, in defining wildlife health priorities, responsibilities, policies and capacity building strategies. The extensive interdisciplinary collaboration needed to manage the many different aspects of wildlife health calls for a more integrated One Health approach.